Law No. 68 of the year 2016 on amending some provisions of law 453 of the year 1954 concerning industrial and trading shops and other rest-disturbing, health detrimental, and dangerous shops / translated by The middle east library for economic services. - The middle east library for economic services, translator. (2025)
Serial No. 39/2016